ANALISIS BANGKRUTNYA SILICON VALLEY BANK (SVB) DAN DAMPAK TERHADAP INDEKS HARGA SAHAM GLOBAL: Studi Empiris Pada Indeks Saham Global The Big Five - Mera Nadia (LPPM Universitas Ekasakti, 2024)
This research aims to evaluate the impact of the bankruptcy of Silicon Valley Bank (SVB) on global stock price indices, especially The Big Five stock index. This research starts from the problem of whether there are significant differences in historical price values ??and market returns before and after SVB's bankruptcy. This research is a comparative study that uses a different paired sample t-test with the SPSS version 25 application. This research compares 15 days before and 15 days after SVB's bankruptcy. The data collected includes historical price values ??and market returns from The Big Five stock index before and after SVB's bankruptcy. Analysis was carried out to see any significant differences that might occur, using statistical tests relevant to the validity of the findings. The research results show that there are significant differences in the historical price values ??and market returns of The Big Five stock index before and after SVB's bankruptcy. The research results show that there are significant differences in the historical price values ??and market returns of The Big Five stock index before and after SVB's bankruptcy. The conclusion of this research is that the bankruptcy event of a large bank such as SVB can disrupt the stability of global stock markets, providing important implications for corporate financial risk management and investors' investment strategies.